Inhibitory failures in cocaine use disorder: Not paying attention when there is a need to be cautious. (1st September 2021) - Howlett, Jonathon R.; Harlé, Katia M.; Paulus, Martin P.
Highlights: Inhibitory control deficits in cocaine use disorder involve both strategic processing and tactical processing. These deficits can be modeled using a Dynamic Belief Model and Hierarchical Drift Diffusion Model in a stop signal paradigm. Subjects with cocaine use disorder were slower to process sensory evidence when expectation of a stop signal was high. This relationship was not present in healthy controls. Abstract: Background: Stimulant use disorders, such as cocaine use disorder, are associated with significant impairment in inhibitory control, which has in turn been linked to difficulties maintaining abstinence following treatment. Here, we combine the Dynamic Belief Model (DBM) and a Hierarchical Drift Diffusion Model (HDDM) to examine whether individuals with cocaine use disorder have both strategic response updating and tactical speed accuracy trade-off problems during inhibitory control. Methods: Twenty-seven individuals with cocaine use disorder and twenty-seven healthy control participants completed a Stop-Signal-Task (SST), in which one has to inhibit a motor response to a prepotent 2-alternative forced choice task on 25 % of the trials. Results: Cocaine use disorder and control subjects did not differ on successful stopping behavior. In cocaine use disorder but not control subjects, higher likelihood of encountering a stop signal was associated with lower drift rate. Moreover, in cocaine use disorder subjects, a more negative relationship between likelihood of encountering a stop signal and drift rate was associated with lower accuracy on stop trials and slower stop reaction time. Conclusions: These results are consistent with a dysregulation between strategic and tactical processing during inhibitory control in cocaine use disorder. Specifically, these individuals are more likely to be less attentive to sensory evidence when the expectation of a stop signal is high.